Medical interns; the neglected learners of the maternity ward learning environment - Masoumeh Rahimi; Fariba Haghani; Shahnaz Kohan; Majid Shirani (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Clinical training during internship is an important part of medical education. The maternity ward is a clinical environment in which medical students pass their obstetrics and gynecology internship to obtain competencies in this field. The present study was conducted to explain medical interns' manner of learning in the maternity ward. MATERIAL AND METHODS: The present study was conducted using a qualitative approach with the inductive content analysis method. This study observed the maternity wards of teaching hospitals affiliated to medical sciences universities of Isfahan and Shahrekord. Data were collected through observation and semi-structured individual interviews. RESULTS: Two main categories and seven subcategories emerged from the analysis of the data. Inadequate participation in learning opportunities included the following three subcategories: the incongruousness of the learning opportunities with the educational goals, inadequate readiness for participation in learning opportunities, and the overlap between learning opportunities and diminished autonomous practice. Inadequate formal and structured education included the following four subcategories: inadequate learning support and direction, subordinate roles and aimless presence, the pale educational role played by the attendants and senior residents, and learning through the support of midwifery educators. CONCLUSION: Participation in and access to learning opportunities in the maternity ward are very difficult for interns. Interns, therefore, need to attend the maternity ward by a structured program and in the company of training supervisors or competent educators to obtain the required competencies in pregnancy and childbirth.